Estimation du sexe fœtal à partir de l’ilium - Pascal Adalian; Sandrine Boutin-Forzano; Marie-Dominique Piercecchi-Marti; Yann Ardagna; Michel Signoli; Ferenc Kosa; Georges Leonetti; Olivier Dutour (Bulletins et Mémoires de la Société d’Anthropologie de Paris, 2001)
Sex estimation is one of the most frequently encountered issues in forensic medicine. While in the case of adults this determination is essentially based on iliac bones and provides a rather reliable classification, there are fewer studies conducted on fetuses and the results are often contradictory.Therefore, we examinated 83 pairs of fetal iliac bones in the Hungarian collection of Fazekas and Kosa and searched for metric criteria that can the best be applied for determining sexual dimorphism. During this research, we tested the different methods proposed for fetal iliac bones and adapted some others used particularly in the case of adults.For this reason, we set up and validated a protocol of taking photographs, as well as a measurement technique developed for numeric pictures with the help of a software program, Adobe Photoshop 6‚.During this study, we selected certain parameters, principally the ones taken on the great sciatic notch, which showed a strong correlation with sex, and we established a logistic regression for estimating the probability of belonging to one sex or the other.The weak percentage of sexual differentiation obtained by this formula led us to take into account age: we organised our sample in different age groups and established a formula that permits correct sex determination in more than 85% of cases (in our sample) for fetuses that are less than 24 gestational weeks old.